Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1108/mip-11-2020-0471
|View full text |Cite
|
Sign up to set email alerts
|

Role of brand experience in predicting consumer loyalty

Abstract: PurposeThis study investigated the role of brand experience dimensions (behavioral, intellectual, sensory and affective) to predict consumer loyalty (repurchase intention (RPI), word of mouth (WOM) and willingness to pay more (WPM)) through the mediating role of perceived brand authenticity (PBA) in the global branding context.Design/methodology/approachA total of 422 consumers participated in this study and provided feedback on top authentic global brands after completing a self-administered online survey. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 78 publications
(122 reference statements)
1
52
1
1
Order By: Relevance
“…Moderating effects Control effects (Hartmann and Ostberg, 2013;Schallehn et al, 2014;Riefler, 2020;Safeer et al, 2021c). These studies demonstrate that consumers respond positively when global brands communicate their authenticity while the contradictory perspectives illustrate the ambiguous function of brand globalness in determining BA's success.…”
Section: Direct Effectsmentioning
confidence: 71%
See 2 more Smart Citations
“…Moderating effects Control effects (Hartmann and Ostberg, 2013;Schallehn et al, 2014;Riefler, 2020;Safeer et al, 2021c). These studies demonstrate that consumers respond positively when global brands communicate their authenticity while the contradictory perspectives illustrate the ambiguous function of brand globalness in determining BA's success.…”
Section: Direct Effectsmentioning
confidence: 71%
“…As a result, many researchers are examining the effects of authenticity through the use of global brands in diverse consumer environments (Hartmann and Ostberg, 2013; Schallehn et al. , 2014; Riefler, 2020; Safeer et al. , 2021c).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a psychological representation that individuals can both steadily exist and temporarily evoke at the same time ( Garbasevschi, 2020 ). Safeer et al (2021c) found that sensory and intellectual experience of brand experience positively influences perceived brand authenticity, which can effectively predict consumer loyalty. Consumer behavior toward brands is influenced by identity constructs ( Leckie et al, 2021 ).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 98%
“…Begitu pula menurut Schmitt (1999) yang membuktikan bahwa pengalaman merek dapat menjadi awal yang baik untuk pembelajaran pada keterikatan antara konsumen dan merek sehingga akhirnya konsumen menjadi loyal dengan merek tersebut. Strategi pemasaran yang mampu meningkatkan pengalaman merek dapat membangun ikatan yang kuat dengan konsumen untuk mencapai loyalitas mereka (Safeer et al, 2021). Lebih lanjut, pengalaman merek juga terbukti memiliki efek langsung positif pada kualitas yang dirasakan, kepercayaan merek dan loyalitas merek dalam konteks produk olah raga (Akoglu dan Ozbek, 2021).…”
Section: Ketidakpastianunclassified